ANALYSIS OF THE POSSIBLE IMPACT OF ROMANIAN AND HUNGARIAN UNIVERSITIES TO ECONOMIC DEVELOPMENT - Gregán, Orsolya Gabriella (Studies and Scientific Researches. Economics Edition, 2023)
Economic development is associated with innovation, which is why the innovation management practices and systems of the universities became essential. This research aimed to benchmark five Romanian and Hungarian universities close to the Romanian-Hungarian border to identify the strengths and weaknesses of the different approaches.The benchmarking included economic data and indicators connected to the innovation of the five biggest universities along the border regions. The analysis was performed using data derived from The Higher Education Word Ranking and Eurostat. For the qualitative part, the web pages of the universities were analyzed.The research found that although the universities on the Hungarian side of the border seem more developed, regional economic development is stronger and more natural on the Romanian side of the border. According to the literature, it is clear that geographical factors play an important role in the development of innovation systems. The closing part of this paper makes an attempt to list the possible causes of the results.